French sociology (New York, 1981)
The book presents a focused, comprehensive review of the social theory of France since 1968. In the introduction, the book illuminates the French intellectual milieu and describes the institutional context in which French sociologists work. Its examination of the French sociological inheritance and the political and economic history that has shaped French thought further helps to clarify the nature and concerns of French social theory and to identify and place individual thinkers. Completing the introductory material, the book outlines the recent history of French sociology
Keywords: france - intellectual life - addresses, essays, lectures,france - sociology - history - addresses, essays, lectures